Warm-up in triathlon: do triathletes follow the scientific guidelines? - Quagliarotti, C.; Villanova, S.; Marciano, A.; López-Belmonte, Ó.; Caporali, C.; Bottoni, A.; Lepers, R.; Piacentini, M. F. (International Journal of Sports Physiology and Performance, 2024)
Purpose: Warming up before competition is universally recognized as an effective way to enhance performance. However, only a few articles have directly investigated different warm-up strategies adopted by triathletes and suggested by coaches. The Olympic-distance triathlon is an endurance competition characterized, at least for the elite, by a fast start with a strong correlation to the final position in the race. Thus, executing a proper warm-up protocol would be beneficial in optimizing performance. The present study aimed to provide an overview of the warm-up protocol adopted/suggested by national-caliber triathletes/coaches before an Olympic-distance triathlon race.